Prospects of differential diagnosis of focal lesion of pancreas by the microRNA assessment - M. S. Kniazeva; T. M. Shestopalova; L. M. Zabegina; A. V. Shalaev; A. K. Ratnikova; V. A. Kashchenko; S. L. Vorobyev; A. V. Malek (Южно-Российский онкологический журнал, 2023)
Purpose of the study. Identification of potential miRNA markers in material of focal pancreatic lesions.Materials and methods. Samples of focal pancreatic lesions after histological evaluation were enrolled in the study including chronic pancreatitis (ChP) (n = 23), low-grade pancreatic intraepithelial neoplasia /PanIN‑1/2 (n = 19), high-grade pancreatic intraepithelial neoplasia /PanIN‑3 (n = 8), and invasive pancreatic ductal adenocarcinoma PDAC (n = 26). Workflow of research included the profiling of cancer-associated miRNA in pooled samples, the selection of potential marker miRNAs, the assessment of selected miRNAs expression in total collection of specimens, the identification of differentially expressed miRNAs, and the approbation of new algorithm of data interpretation via ratio of “reciprocal miRNA pair”. Consequent reactions of revers transcription and quantitative teal-time PCR were used.Results. The expression levels of miR‑216a and miR‑217 were decreased in the following order: PanIN‑1/2 > PanIN‑3 > PDAC. Moreover, miR‑375 was up-regulated while miR‑143 was down-regulated in the PDAC. Differential diagnostics of PDAC versus focal chronic pancreatitis might be performed with high accuracy (AUC > 0.95) by assessment panel of four molecules: miR‑216a, miR‑217, miR‑1246 and Let‑7a.Conclusion. The assessment of microRNAs in pancreatic lesions is a promising approach for the differential diagnosis of PDAC, but this technology requires further validation with an increase in the number of samples.